Probing the Effects of Transformational Leadership on Employees' Job Satisfaction With Interaction of Organizational Learning Culture. (June 2020) - Khan, Saif-Ur-Rehman; Anjam, Mahwish; Abu Faiz, Mohammad; Khan, Faisal; Khan, Hashim
The purpose of this study is to explore how various dimensions of leadership style are being used to measure organizational effectiveness. Job satisfaction is one of the essential indicators used to measure organizational effectiveness. Literature suggests that the manager's transformational leadership style highly influences the employees' job satisfaction. This study focuses on identifying the role of a transformational leader in developing job satisfaction in employees of the banking industry, using the organizations' learning culture as the moderating variable. For this purpose, a total of 180 respondents were surveyed from UAE's banking sector. In this study descriptive statistics, Pearson's correlation coefficient, and multiple regression analysis were employed for the data analyses. The results confirmed that the five dimensions of transformational leaders and overall transformational leadership style significantly affect the employee's job satisfaction, whereas the moderating effect of the organizational learning culture on any of the said relationships was found insignificant. This study used self-reported data based on a cross-sectional survey in the banking sector only. The research emphasizes the implication of the leaders' personal traits to be a significant determinant of an employee's satisfaction. In addition, managers in the banking sector in UAE realized that organization learning culture (OLC) has not had any significant impact on employees' job satisfaction. As there is not sufficient literature on the moderating role of organizational learning culture, this study is a valuable contribution to the existing body of knowledge.